IP-10 and MIG are sensitive markers of early virological response to HIV-1 integrase inhibitors - Álvarez, Hortensia; Gutiérrez-Valencia, Alicia; Mariño, Ana; Saborido-Alconchel, Abraham; Calderón-Cruz, Beatriz; Pérez-González, Alexandre; Alonso-Domínguez, Jacobo; Martínez-Barros, Inés; Gallego-Rodríguez, María; Moreno, Santiago; Aldamiz, Teresa; Montero-Alonso, Marta; et al. (Frontiers in Immunology, 2023)
Interferon-inducible protein-10 (IP-10) and Monokine induced by interferon-gamma (MIG) are chemokines recognized as inflammatory biomarkers during HIV-1 infection. We assessed their early and long-term dynamics after initiation of antiretroviral treatment (ART).Persons with HIV-1 (PWH) aged>18 years starting their first ART in 2015-2021 in a prospective cohort (n=73) were included. IP-10 and MIG plasma levels were quantified using a multiplexed bead-based assay.IP-10 and MIG plasma levels showed a significant and consistent reduction following ART (80% integrase inhibitor [INSTI]-based) initiation, starting at day 20 and maintained throughout time (48 months), paralleling the HIV-1 RNA decay and CD4+ count recovery (p<0•001).At baseline, PWH50 years, CDC stage C and CD4+ count<350cells/mm 3 had higher levels of IP-10 (p=0•022, p=0•001 and p=0•002, respectively) and MIG (p<0•001, p=0•024 and p=0•069, respectively). All them matched their counterparts several months following ART initiation. MIG levels showed a greater decrease at day 10 in those treated with INSTI (p=0•038). Low-level HIV-1 viremia did not impact MIG or IP-10 levels.Plasma IP-10 and MIG showed an early significant decline following ART initiation, with greater MIG early declines in INSTI-based regimens. These findings suggest a strong impact of HIV-1 viremia on IP-10 and MIG levels. 332 (149-672) 323 (54-663) 376 (222-716) c Baseline CD4+ T < 350 cells/mm 3 , n (%) 36 (49•3) 23 (56•0) 13 (40•0) c Baseline CD4+T/ CD8+ T cell ratio; median (IQR) 0•35 (0•15-0•59) 0•29 (0•11-0•59) 0•43 (0•15-0•62) c Baseline HIV-1 RNA, copies/mL; median (IQR) 58,100 (13,966-338,000) 87,600 (19,400-552,500) 29,192 (2,636-98,690) c Baseline HIIV-1 RNA >100,000 copies/mL, n (%) 28 (38•3) 20 (48•7) 8 (25•0) HIV genotype B, n (%) Non-B, n (%) --19 (46•3)